2012
DOI: 10.1007/s10948-012-1959-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Superconducting MgB2 Thin Films by Magnetron co-Sputtering on (001) MgO Substrates

Abstract: We fabricated superconducting MgB2 thin films on (001) MgO substrates. The samples were prepared by magnetron rf and dc co-sputtering on heated substrates. They were annealed ex-situ for one hour at temperatures between 450 • C and 750 • C. We will show that the substrate temperature during the sputtering process and the post annealing temperatures play a crucial role in forming MgB2 superconducting thin films. We achieved a critical onset temperature of 27.1 K for a film thickness of 30 nm. The crystal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(41 reference statements)
0
1
0
1
Order By: Relevance
“…The working pressure in the chamber was 5.3 • 10 −3 mbar, with argon used as the plasma-forming gas with a purity of 99.9999%. The base vacuum in the magnetron sputtering chamber did not exceed 8 The substrate temperature during deposition was maintained at 282 • C, chosen based on previous studies [28][29][30][31][32][33][34][35] that demonstrated the highest T c films resulted from sputtering onto substrates within the temperature range of 270…”
Section: Experimental Details Part and Methodsmentioning
confidence: 99%
“…The working pressure in the chamber was 5.3 • 10 −3 mbar, with argon used as the plasma-forming gas with a purity of 99.9999%. The base vacuum in the magnetron sputtering chamber did not exceed 8 The substrate temperature during deposition was maintained at 282 • C, chosen based on previous studies [28][29][30][31][32][33][34][35] that demonstrated the highest T c films resulted from sputtering onto substrates within the temperature range of 270…”
Section: Experimental Details Part and Methodsmentioning
confidence: 99%
“…Среди таких методов -совместное испарение компо-нент из резистивных испарителей [4], а также испарение одного из компонентов из резистивного испарителя, а другого с помощью электронной пушки [5], лазерное осаждение с последующим ex situ отжигом [6], молекулярно-лучевая эпитаксия [7], магнетронное распыление мишеней [8,9], осаждение путём гибридного физико-химического испарения (hybrid physical-chemical vapour deposition (HPCVD)) [10][11][12][13]. Каждый метод имеет преимущества и недостат-ки, для сравнения в табл.…”
Section: Introductionunclassified
“…Prior investigations using Θ-2Θ x-ray diffraction measurements have shown that sputtered MgB 2 crystals are perpendicularly oriented on the surface plane independent of the choice of substrate [16]. Using the Scherrer formula, a perpendicular grain size of 7 nm could be estimated.…”
mentioning
confidence: 99%